Fully automated radiosynthesis of [68Ga]Ga-FAPI-46 with cyclotron produced gallium - Adam J. Rosenberg; Yiu-Yin Cheung; Fei Liu; Carina Sollert; Todd E. Peterson; Jonathan A. Kropski (SpringerOpen, 2023)
Abstract Background Radiopharmaceuticals capable of targeting the fibroblast activation protein have become widely utilized in the research realm as well as show great promise to be commercialized; with [68Ga]Ga-FAPI-46 being one of the most widely utilized. Until now the synthesis has relied on generator-produced gallium-68. Here we present a developed method to utilize liquid-target cyclotron-produced gallium-68 to prepare [68Ga]Ga-FAPI-46. Results A fully-automated manufacturing process for [68Ga]Ga-FAPI-46 was developed starting with the 68Zn[p,n]68Ga cyclotron bombardment to provide [68Ga]GaCl3, automated purification of the [68Ga]GaCl3, chelation with the precursor, and final formulation/purification. The activity levels produced were sufficient for multiple clinical research doses, and the final product met all release criteria. Furthermore, the process consistently provides < 2% of Ga-66 and Ga-67 at the 4-h expiry, meeting the Ph. Eur. standards. Conclusions The automated radiosynthesis on the GE FASTlab 2 module purifies the cyclotron output into [68Ga]GaCl3, performs the labeling, formulates the product, and sterilizes the product while transferring to the final vial. Production of > 40 mCi (> 1480 MBq) of [68Ga]Ga-FAPI-46 in excellent radiochemical yield was achieved with all batches meeting release criteria.